EXPLORING THE KEY DETERMINANTS OF ENTREPRENEURIAL INTEREST: AN EMPIRICAL STUDY AMONG STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, MALIKUSSALEH UNIVERSITY - Miftahul Jannah (CV. RADJA PUBLIKA, 2025)
This study aims to analyze the factors influencing entrepreneurial interest among students at the Faculty of Economics and Business, Malikussaleh University. The sample consisted of 120 students from various majors, predominantly from Entrepreneurship, Management, and Accounting programs. A multiple linear regression analysis was employed, with entrepreneurial interest as the dependent variable and independent variables including self-confidence, family support, business knowledge, risk tolerance, entrepreneurial skills, and campus support. The analysis revealed that selfconfidence (coefficient = 0.393432) and family support (coefficient = 0.468088) significantly positively impact entrepreneurial interest, while risk tolerance (coefficient = -0.424534) demonstrated a significant negative relationship. These findings underscore the importance of strengthening social support and enhancing self-confidence to facilitate entrepreneurial interest among students. This study recommends that educational institutions enhance programs that foster entrepreneurial skills and social networks to boost students' interest in entrepreneurship.